An achievement test for the remedial English students of the Mindanao State University - Gonzalez, Eunice R. (1972)
There is a pressing need for better and more effective means of evaluation in the field of education today. It was in answer to this call that this study - a construction of an achievement test for the remedial English students of the Mindanao University - is done. A test for learners with different linguistic backgrounds, it consists of items testing problems on three language aspects - structure, vocabulary, and reading. The difficulty of the test lies in the students' deficient vocabulary and reading skills. It is recommended that the teaching and development of the skills for vocabulary and reading be given emphasis in English A through a creation of a reading program and the revision of the instructional materials for the course.
Thesis (M.A.T. English)--University of the Philippines.
Keywords: English language -- Examinations